The three pathways to becoming a midwife: self-assessed confidence in selected competencies in intrapartum care from seven African countries. (2nd March 2021) - Lindgren, Helena; Hildingsson, Ingegerd; Christensson, Kyllike; Bäck, Lena; Mudokwenyu–Rawdon, Christina; Maimbolwa, Margaret C; Laisser, Rose Mjawa; Omoni, Grace; Chimwaza, Angela; Mwebaza, Enid; Kiruja, Jonah; Sharma, Bharati
Abstract : Background/Aims: Globally, there are three pathways to become a midwife: midwifery post nursing, direct entry midwifery and integrated nursing and midwifery. There is limited knowledge on the effectiveness of pre-service midwifery education. The aim of this study was to describe and compare midwifery students' confidence in intrapartum skills and associated factors such as type and level of education. Methods: A multi-country cross-sectional study was conducted, where midwifery students were approached in the final months of their education programme. Data were collected using a questionnaire, based on the basic skills by the International Confederation of Midwives. Intrapartum care comprised 40 skills. Results: In total, 1407 midwifery students from seven sub-Saharan countries responded. The 40 skills were grouped into six domains; three related to care during the first and second stage of labour and three related to care during the third stage of labour. Sex and age were significantly associated with confidence, with female students and those 26–35 years old having higher levels of confidence. Students enrolled in a direct entry programme were more confident than other students in all three domains of care related to the first and second stage of labour. Conclusions: Direct entry was found to result in higher confidence for midwifery students than post nursing programmes or integrated programmes. Further research is needed for evaluation of competence.